Legal Assistance in the Development of Tourism Villages by Optimizing the Role of Village Institutions in the Village of Bongan Tabanan Bali - I Dewa Agung Gede Mahardika Martha; IB. Agustya Mahaputra; I Made Aditya Mantara Putra (Community Service Journal of Law, 2024)
This research discusses the importance of legal assistance in the development of tourism villages in Bongan Village, Tabanan, Bali, with a focus on strengthening the role of Village-Owned Enterprises (BUMDes) and Tourism Awareness Groups (Pokdarwis). The main obstacles faced are the absence of Village Regulations (Perdes) that specifically regulate the roles of these two institutions as well as the lack of legal understanding related to tourism management and effective marketing strategies. Legal assistance aims to provide an understanding of regulations, assist in drafting relevant Perdes, and reduce legal risks in cooperation with third parties. In addition, training in management and marketing based on digital technology is expected to support the optimization of village tourism potential. The results showed that collaboration between legal aspects, management, and digital technology plays an important role in realizing sustainable tourism village development and improving the welfare of local communities. Synergy between the village government, educational institutions, business actors, and the community is needed to make Bongan Village a model of local wisdom-based tourism villages in Bali. Using an empirical legal approach, this research provides applicable recommendations that can be adopted by other tourist villages in Bali and regions with similar contexts.